Is Digital Financial Inclusion Unlocking Growth? - Khera, Purva (IMF Working Papers; Working Paper ;, 2021)
Digital financial services have been a key driver of financial inclusion in recent years. While there is evidence that financial inclusion through traditional services has a positive impact on economic growth, do the same results carry over for digital financial inclusion? What drives digital financial inclusion? Why does it advance more in some countries but not in others? Using new indices of financial inclusion developed in Khera et. al. (2021), this paper addresses these questions for 52 developing countries. Using cross-sectional instrument variable procedure, we find that the exogenous component of digital financial inclusion is positively associated with growth in GDP per capita during 2011-2018, which suggests that digital financial inclusion can accelerate economic growth. Fractional logit and random effects empirical estimation identifies access to infrastructure, financial and digital literacy, and quality of institutions as key drivers of digital financial inclusion. These findings are then used to help inform policy recommendations in areas related to the digitization of financial services to promote financial inclusion.